Evaluación de la gestión administrativa en el Centro de Salud de la ciudadela Los Sauces-Cantón Urdaneta - Llumitaxi García, Carmen Leonor (2020)
The present research work is: "The evaluation of the administrative management in the health center of Ciudadela los Sauces had as its purpose the relationship between administrative management and the quality of care for users in the Administration Locality of the health center the willows, The method to be used is qualitative and is applied because the analysis of the problematic situation of the Health Center is carried out on the inadequate administrative management that it maintains and in turn a synthesis of the problems that remains in this Institution is related. The tool is the survey applied to internal and external clients to learn more about the reality of what is happening in the administrative management of the Los Sauces-Catarama Health Center. The problematic situation of the Sauces Health Center of the Catarama parish, is the administrative process for care have not been modified and adapted to the new trends and manifestations of patients and their Primary Health Care network. Keywords. Administrative management and quality of service. Which would have to meet their expectations and needs, it should be noted that the aforementioned institution does not have the physical space necessary for the doctors to be able to fully comply with their functions and this makes it impossible for the care provided to users to be according to your needs.